PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KOMITMEN ORGANISASI KARYAWAN MEDIS PADA RSIA ERIA BUNDA PEKANBARU - Khafis Inggil Cahya; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine and examine the influence of Work Environment and Motivation to Organizational Commitment of medical employees RSIA Eria Bunda Pekanbaru which is located at JL.K.H. Ahmad Dahlan No.163 Sukajadi-Pekanbaru. Respondents in this study amounted to 70 medical employees of RSIA Eria Bunda Pekanbaru. This study uses quantitative approach, this research data obtained through questionnaire in the form of research questions that have been filled by respondents who have been determined. Data analysis method used in this study is multiple linear regression analysis performed using SPSS software.The results of this study prove that the Work Environment (X1) has a positive and significant influence on Organizational Commitment (Y). This can be seen from the value of t count greater than t table (9.092> 1.995) and level sig. (0.000 <0.05).This means that the Work Environment variables significantly influence the Organizational Commitment. Work Motivation (X2) has a positive and significant influence on Organizational Commitment (Y).This can be seen from the value of t arithmetic greater than r table (9.4.36> 1.995) and sig. (0.000 <0.05). This means that motivational variables have a significant effect on Organizational Commitment.From the simultaneous test results obtained from the results of F count is 57.745 while the F table value is 3.13. This means F arithmetic> F table and significance value 0,000 <alpha 0,05. Means that the Work Environment (X1) and Motivation (X2) simultaneously have a significant effect on Organizational Commitment (Y).Keywords: Work Environment (X1), Motivation (X2), Organizational Commitment (Y)